Rents, the moral economy of remittances, and the rise of a new transnational development model - Hannes Warnecke-Berger (Revue de la Régulation)
World remittances accounted for 714 billion $US in 2018 of which 550bn $US flew to the Global South. In today’s Global South, remittances are a major source of foreign exchange earnings. Remittances increasingly question the notion of the Global South as a commodity and raw material exporter. This article integrates remittances into rent theory. It argues for a broader understanding of rents and uses the explanatory power of rent theory. Conceptually, the article differentiates between sources of rent and their mode of appropriation. The article situates the causes for remittances both on a macro structural level in uneven global development and resulting inequalities as well as on the micro level within translocal moral economies between potential remittance senders in migratory host economies and their home economies. Remittances originate in global inequalities and the transnationalization of labor markets. Remittances are mediated through currency exchange rates, but remittances are negotiated within translocal moral economies. The article proposes to conceptualize remittances as labor differential rents. These rents give rise to a new transnational development model and an increasing number of economies specialize on remittances for their own social reproduction. Finally, the article points to the peculiarities of this development model: remittance-rents indirectly stabilize elite rule and shift political accountabilities from the political system to within transnational families. With the analysis of remittances, the article adds new structural economic mechanisms and institutional modes of rent appropriation that rent theory has thus far neglected.